Pengaruh Total Asset Turn Over dan Sales Growth Terhadap Return on Asset pada PT Fks Food Sejahtera Tbk - Windari, Kurnia Wardani; Puji Muniarty; Alwi (Jurnal Ilmu Manajemen Retail Universitas Muhammadiyah Sukabumi, 2025)
The purpose of this research is to examine how increasing sales and total asset turnover (TATO) affect PT FKS Food Sejahtera Tbk's return on assets (ROA). Associative research of this kind is quantitatively approached in this work. The financial statements of the corporation for the years 2014–2023, which are considered secondary data, are used. A combination of the t-test, F-test, and multiple linear regression with classical assumption testing is used for the study. According to the findings, ROA was unaffected by changes in Total Asset Turnover (TATO) or sales growth. Concurrently, ROA is unaffected by any of the two factors. According to these findings, the company's overall profitability performance over the research period cannot be explained by effective use of assets or increase in sales. To provide a fuller picture of the elements influencing ROA, future studies should take into account other financial and non-financial aspects.